Comparative analysis of diabetes risk in patients with obstructive sleep apnea undergoing different treatment approaches - Nai-Chen Shih; James Cheng-Chung Wei (Journal of Otolaryngology - Head and Neck Surgery)
Abstract The bidirectional relationship between obstructive sleep apnea (OSA) and diabetes mellitus (DM) has been explored in several studies. O’Connor-Reina et al., published a paper entitled: “Risk of diabetes in patients with sleep apnea: comparison of surgery versus CPAP in a long-term follow-up study” to examine a cohort study comparing the effects of surgery and continuous positive airway pressure (CPAP) on the risk of diabetes in patients with OSA. The study findings suggest that both therapies offer protection against diabetes, with upper airway surgery demonstrating better preventive efficacy than CPAP. However, potential biases and confounding variables should be considered, such as race, ethnicity, socioeconomic factors, BMI, glucose levels, HbA1c values, medication use and healthy dietary habits. Besides using International Classification of Diseases codes, the definition of DM as an outcome can also incorporate specific laboratory indicators and the use of diabetes treatment medications. Furthermore, subgroups analysis defined by demographic variables, such as age, sex, and race is recommended. The limitations of the study also include potentially data omissions due to reliance on electronic medical records from specific healthcare institutions. To enhance research comprehensiveness, alternative data sources and collaborations with additional healthcare institutions are suggested for future investigations.